Réponses

2014-02-10T23:00:24+01:00
Bonsoir,

J'ai fait ce que j'ai pu pour déchiffrer ton énoncé :)

A=\dfrac{13\times10^9\times10^{-6}}{2}=\dfrac{13}{2}\times(10^9\times10^{-6})\\\\=6,5\times10^{9-6}\\\\=6,5\times10^{3}\\\\=6,5\times1000\\\\=6500


B=\dfrac{2\times10^{-3}\times5}{10^{-5}}=\dfrac{2\times5\times10^{-3}}{10^{-5}}=\dfrac{10\times10^{-3}}{10^{-5}}\\\\=\dfrac{10^1\times10^{-3}}{10^{-5}}\\\\=\dfrac{10^{1-3}}{10^{-5}}\\\\=\dfrac{10^{-2}}{10^{-5}}\\\\=10^{-2-(-5)}=10^{-2+5}=10^3\\\\=1000


C=\dfrac{15\times(10^{-1})^3\times8}{24\times10^{-3}}=\dfrac{15\times8\times10^{-1\times3}}{24\times10^{-3}}=\dfrac{120\times10^{-3}}{24\times10^{-3}}\\\\=\dfrac{120}{24}\times\dfrac{10^{-3}}{10^{-3}}\\\\=5\times1\\\\=5